Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Outsourcing Di Mediasi Employee engagement - Trisninawati Trisninawati; Efan Elpanso (MBIA, 2021)
This study examines the mediating role of employee engagement on the effect of work motivation and work environment on in-role performance. Respondents in this study were employees of PT Trans Dana Profitri outsourcing, which is a company that provides labor services totaling 100 respondents. The sample was carried out by purposive sampling, the data was collected by means of a survey through a questionnaire using a Likert scale with a Structural Equation Modeling (SEM) approach using AMOS version 24, a significance level of 5% to analyze the data. The results showed that motivation had a positive effect on employee engagement = 0, 482, p 0.0001<0.13), Work Environment had a positive effect on employee engagement (β= 0.360 P <0.049), Employee engagement had a positive effect on performance in role ( = 0.455 P <0.0***), work motivation has a positive effect on in-role performance (β= 0549, P <0.002, work environment has a negative effect on in-role performance (β= -0, 133 P <0.365), The results of the employee engagement mediation test mediate the effect of the work environment on in-role performance as evidenced by the indirect effect value of 0.188 which is greater than the direct effect of -0.153, meaning that hypothesis 6 is proven, employee engagement does not mediate the effect of work motivation on in-role performance, which is indicated by the value indirect effect .241 is smaller than direct effect .604 means that hypothesis 7 is not proven. Keywords: work motivation, work environment, employee engagement, performance in role Abstrak Penelitian ini menguji peran mediasi employee engagement pada pengaruh motivasikerja dan lingkungan kerja terhadap kinerja in role. Responden penelitian ini dilakukan pada karyawan outsourcing PT PT Trans Dana Profitri merupakan perusahaan yang menyediakan jasa tenaga kerja berjumlah 100 responden. Sampel dilakukan dengan purposive sampling, pengumpulan data dilakukan dengan survey melalui kuesioner menggunakan skala Likert dengan pendekatan metode Structural Equation Modelling (SEM) menggunakan AMOS versi 24, tingkat signifikansi 5 % untuk menganalisis data. Hasil penelitian menunjukkan motivasi berpengaruh positif terhadap employee engagement β= 0, 482, p 0,0001<0,13), Lingkungan Kerja berpengaruh positif terhadap employee engagement (β= 0,360 P <0,049), Employee engagement berpengaruh positif terhadap kinerja in role (β= 0,455 P <0,0***), Motivasi Kerja berpengaruh positif terhadap kinerja in role (β= 0549, P <0,002, Lingkungan Kerja berpengaruh negatif terhadap Kinerja in role (β= -0, 133 P <0,365), Hasil uji mediasi employee engagement memediasi pengaruh lingkungan kerja terhadap kinerja in role dibuktikan dengan nilai pengaruh tidak langsung 0,188 lebih besar dari pada pengaruh langsung -0,153, berarti hipotesis 6 terbukti, employee engagement tidak memediasi pengaruh motivasi kerja terhadap kinerja in role, yang ditunjukkan dengan nilai pengaruh tidak langsung ,241 lebih kecil dari pada pengaruh langsung ,604 berarti hipotesis 7 tidak terbukti. Kata kunci: motivasi kerja, lingkungan kerja, employee engagement, kinerja in role